Epiprofin Transcriptional Activation Promotes Ameloblast Induction From Mouse Induced Pluripotent Stem Cells via the BMP-Smad Signaling Axis - Miao, Xinchao; Niibe, Kunimichi; Fu, Yunyu; Zhang, Maolin; Nattasit, Praphawi; Ohori-Morita, Yumi; Nakamura, Takashi; Jiang, Xinquan; Egusa, Hiroshi (Frontiers in Bioengineering and Biotechnology, 2022)
The transcriptional regulation of induced pluripotent stem cells (iPSCs) holds promise for their directed differentiation into ameloblasts, which are usually lost after tooth eruption. Ameloblast differentiation is regulated by multiple signaling molecules, including bone morphogenetic proteins (BMPs). Epiprofin (Epfn), a transcription factor, is expressed in the dental epithelium, and epithelial Epfn overexpression results in ectopic ameloblast differentiation and enamel formation in mouse incisor, a striking phenotype resembling that of mice with deletion of follistatin (a BMP inhibitor). However, it remains unknown whether and how Epfn transcriptional activation promotes ameloblast induction from mouse iPSCs. Here, we generated doxycycline-inducible Epfn-expressing mouse iPSCs (Epfn-iPSCs). Ameloblasts, which are characterized by positive staining for keratin 14 and amelogenin and alizarin red S staining, were successfully derived from Epfn-iPSCs based on a stage-specific induction protocol, which involved the induction of the surface ectoderm, dental epithelial cells, and ameloblasts at stages 1, 2, and 3, respectively. Epfn activation by doxycycline at stages 2 and/or 3 decreased cell proliferation and promoted ameloblast differentiation, along with the upregulation of p-Smad1/5/8, a key regulator of the BMP-Smad signaling pathway. Gene analysis of the BMP-Smad signaling pathway-associated molecules revealed that Epfn activation decreased follistatin expression at stage 2, but increased BMP2/4/7 expression at stage 3. Perturbations in the ameloblast differentiation process were observed when the BMP-Smad signaling pathway was inhibited by a BMP receptor inhibitor (LDN-193189). Simultaneous LDN-193189 treatment and Epfn activation largely reversed the perturbations in ameloblast induction, with partial recovery of p-Smad1/5/8 expression, suggesting that Epfn activation promotes ameloblast induction from mouse iPSCs partially by upregulating BMP-Smad activity. These results reveal the potential regulatory networks between Epfn and the BMP-Smad pathway and suggest that Epfn is a promising target for inducing the differentiation of ameloblasts, which can be used in enamel and tooth regeneration.